Investigation of a norovirus outbreak among hospital staff in Zhejiang, China: tracing the source to contaminated “red bean cake” - Duan, Xiaojian; Wang, Jing; Wang, Yi; He, Zhaokai; Ren, Xiaobin; Wang, Zhe; Kao, Qingjun; Song, Kai; Huo, Liangliang (Frontiers in Public Health, 2025)
While nosocomial norovirus transmission in hospitalized patients is well characterized, its transmission dynamics among HCWs remain poorly documented. This investigation of HCW-focused norovirus transmission provides critical epidemiological evidence to refine infection control protocols for gastroenteritis in healthcare settings. This study utilized a retrospective case–control design to systematically analyze outbreak transmission dynamics. Structured questionnaires were implemented ≤72 h post-symptom onset to capture dietary exposures during the three-day exposure window, minimizing recall bias. Potential high-risk dining periods and food items were further analyzed via a case-control study. The outbreak investigation identified 52 cases, including 48 HCWs and 4 cafeteria staff, yielding an overall attack rate of 2.21% (52/2352). Epidemiological evidence supports a point-source origin, as demonstrated by the single-peak epidemic curve. Case–control analysis revealed the lunch on 19th June as the primary exposure window (statistically significant OR = 25.21; 95% CI: 3.35–189.69), with the “red bean cake” served in the implicated meal being the significantly associated food item (OR = 1248.75; 95% CI: 170.64–9138.33). RT-qPCR confirmed norovirus GII RNA in clinical specimens from cases and the implicated “red bean cake” food sample. These findings definitively established the “red bean cake” as the outbreak’s etiological source.